Evaluación nutricional y control del régimen alimentario de niños que estudian en dos jardines asistidos por Qali Warma, Alto Trujillo, noviembre -diciembre 2018 - Dominguez Iparraguirre, Kely Lizbeth (2019)
In the present work, the nutritional evaluation and control of the diet of the children studying in gardens assisted by Qali Warma, Alto Trujillo 2018 was carried out. The nutritional evaluation was carried out by anthropometric methods, according to the WHO reference tables. To control the diet, the 24-hour reminder method was used. According to the BMI, it was found that 73% of the children of the I.E N ° 2193 present a normal nutritional status; 7% overweight, 7% severe thinness and 13% thinness risk. In the Darío Celis Vásquez institution it was found that children have 86% of obesity, 7% of children have a normal nutritional status and 7% are overweight. According to the indicator (T / E), 100% of the children who attend the Darío Celis Vásquez garden have a normal nutritional status, and those who attend the Educational Institution No. 2193, 93% have a normal nutritional status and 7% risk of short stature. 69% of children in the gardens assisted by Qali Warma, Alto Trujillo-2018 have a normal diet, 24% have an excessive caloric intake and 7% have a deficit. It is concluded that the nutritional status of children of both institutions is normal in more than 50% and their diet also